Sistem Pakar Menggunakan Metode Certainty Factor dalam Identifikasi Pengembangan Minat dan Bakat Khusus pada Siswa - Nandra Sunaryo; Y Yuhandri; S Sumijan (Jurnal Sistim Informasi dan Teknologi, 2021)
Identification of the development of special interests and talents needs to be done in order to find out the potential of students. This knowledge is needed by the teacher when providing counseling guidance to students in order to know the types of special interests and talents of students. This study aims to identify the development of special interests and talents in students based on the characteristics of special interests and talents appropriately. In this study using the Certainty Factor method where this expert system can assist experts in identifying the development of special interests and talents based on the characteristics of special interests and talents in students. Followed by calculating the level of accuracy with the results of the counseling guidance teacher analysis. The results of the testing of the Certainty Factor method were successfully applied by comparing the data with the system that had been designed so that a good level of accuracy was obtained from the results of the system calculations with expert decisions of 80% of the 5 test data. This expert system application can be used as an alternative in identifying the development of special interests and talents in students.